Radio navigation and photodynamic methods for intraoperative visualization of the parathyroid glands (review of literature) - P. N. Romashchenko; N. A. Maistrenko; D. S. Krivolapov; D. O. Vshivtsev (Вестник хирургии имени И.И. Грекова)
Intraoperative identification of healthy parathyroid and parathyroid adenomas facilitate a favorable outcome of surgical treatment of patients with parathyroid diseases and various hyperparathyroidism’s forms. In doing so, it is important to preserve the entire parathyroid tissue, since unintentional damaging, removal or devascularization leads to the most common development of complication – hypoparathyroidism, which occasionally becomes permanent. Although, in case of surgical treatment of patients with hyperparathyroidism, the removal of the whole pathologically altered tissue is needed in order to avoid the persistence and recurrence hyperparathyroidism, as confirmed by intraoperative and postoperative parathyroid hormone examination. Up to recent time, surgeons could had relied only on pre-surgical localization of hyperfunctioning parathyroid glands, thorough knowledge of front neck anatomy and personal experience, which wasn’t always reliable to recognize the parathyroids intraoperatively and differentiate the healthy parathyroid tissue from adenoma. To solve these problems, the auxiliary navigation and visualization methods, based on application of radiopharmaceutical and fluorescent agents, tropic to parathyroid tissue, are being actively implemented to endocrine surgery nowadays. The comparative characteristic of modern methods for intraoperative visualization of the parathyroid glands, based on the worldwide literature data, is represented in this article.